Factors That Affect the Value of Non-Financial Companies in Indonesia - Saputro, Dio Bimo; Afaqa Hudaya; Hermajiwandini, Chandra Murti Dewi Widowati (Journal of Financial and Behavioural Accounting, 2024)
Abstract The purpose of this study is to examine the variables that affect business value. These elements consist of company size, leverage, profitability, liquidity, and dividend policy as a moderating variable. Non-financial enterprises that were listed on the Indonesia Stock Exchange between 2021 and 2023 make up the research's population. Purposive sampling was used to choose the sample, and 102 businesses satisfied the requirements. Multiple regression analysis is used in the study to process the data. The results show that business value is highly impacted by profitability, liquidity, profitability, and leverage, all of which are regulated by dividend policy. On the other hand, firm value is not significantly impacted by liquidity, leverage, firm size, dividend policy, or firm size moderated by dividend policy.